2000
DOI: 10.1104/pp.124.3.1039
|View full text |Cite
|
Sign up to set email alerts
|

Localization of a Nod Factor-Binding Protein in Legume Roots and Factors Influencing Its Distribution and Expression

Abstract: The roots of the legume Dolichos biflorus contain a lectin/nucleotide phosphohydrolase (Db-LNP) that binds to the Nod factor signals produced by rhizobia that nodulate this plant. In this study we show that Db-LNP is differentially distributed along the surface of the root axis in a pattern that correlates with the zone of nodulation of the root. Db-LNP is present on the surface of young and emerging root hairs and redistributes to the tips of the root hairs in response to treatment of the roots with a rhizobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 63 publications
(47 reference statements)
2
36
0
Order By: Relevance
“…In most legumes, two types of apyrase are present; a legume-specific APY1-type apyrase and an APY2-type apyrase. Apyrases of the legume-specific type, such as DbLNP and GS52, are known to function in Rhizobiumlegume symbiosis (Day et al, 2000;Kalsi and Etzler, 2000;McAlvin and Stacey, 2005;Govindarajulu et al, 2009). In this study, no cDNA clone belonging to the legume-specific apyrase family was obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most legumes, two types of apyrase are present; a legume-specific APY1-type apyrase and an APY2-type apyrase. Apyrases of the legume-specific type, such as DbLNP and GS52, are known to function in Rhizobiumlegume symbiosis (Day et al, 2000;Kalsi and Etzler, 2000;McAlvin and Stacey, 2005;Govindarajulu et al, 2009). In this study, no cDNA clone belonging to the legume-specific apyrase family was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of MP67 was higher than that of MpAPY2, telling us that MP67 plays a role distinct from conventional apyrase. The legume-specific apyrases such as DbLNP (Etzler et al, 1999) from D. biflorus and GS52 (Day et al, 2000;Kalsi and Etzler, 2000) from G. soja are localized to the cell membrane and are known to function in the nodulation of legumes. Potato (Solanum tuberosum)-specific apyrase has a signal sequence and is apoplastically localized in tissues (Riewe et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The localization of LNP to legume root hair cells, its rhizobiainduced accumulation at root hair tips, the ability of LNP antiserum to interfere with nodulation Kalsi and Etzler, 2000), and the finding that silencing LNP in soybean reduces nodulation (Govindarajulu et al, 2009) all pointed to a function for LNP in nodulation signaling. In this work, we inhibited the formation of LNP and revealed that in three independent antisense lines, there was no nodulation following inoculation with M. loti.…”
Section: Discussionmentioning
confidence: 99%
“…LNP can be detected around the surface of root hairs using immunofluorescence (Kalsi and Etzler, 2000;Fig. 1E).…”
Section: Isolation Of Stable Antisense Transformants Lacking Lnpmentioning
confidence: 99%
See 1 more Smart Citation